Transanal Hemorrhoidal Dearterialization (THD): A Single Center Experience on 100 Consecutive Cases - Mitevski, Aleksandar; Cvetanovski, Vladko; Markov, Petar; Milev, Ilija (Lietuvos chirurgija, 2024)
Introduction. Surgeons, using all available means for the treatment of the hemorrhoidal disease, must make compromises between the radicality of the potential surgical treatment (to prevent recurrence) and the maintenance of the postoperative functionality of the anorectum (avoiding stricture, anal fissures, incontinence, reduction of postoperative pain etc.). Materials and methods. All patients treated with the THD method using a system manufactured by THD S.p.A., Correggio, Italy, consisting of a proctoscope equipped with a Doppler probe and a light source was used to perform the operation. Results. Out of 100 operated patients, 64 (64%) were men and 36 (36%) were women. 54 patients had third degree hemorrhoidal disease, 32 had fourth degree, 7 patients had fourth degree hemorrhoidal disease with active bleeding and 7 patients had second degree hemorrhoidal disease with active bleeding. In the follow-up period, anal fissure formation in two patients and prolapse of a hemorrhoidal node in a treated patient with fourth-degree hemorrhoidal disease were noted. Discussion. It is estimated that more than 50% of the general population will experience at least one episode of symptomatic hemorrhoids during their lifetime. Morphological and hemodynamic changes that occur in patients with hemorrhoidal disease is the finding of an increased diameter of the terminal branches of the superior rectal artery that supplies the hemorrhoidal nodes. These branches are 10–11 in number, of which ligation of up to six is allowed for effective treatment with the THD method. Conclusion. If the THD technique is used according to the established standards, postoperative complications in patients in the form of fecal incontinence and chronic pain have not been described, which is also confirmed in our series. The absence of serious complications while addressing a hemorrhoidal disease at the level of the cause of its occurrence, makes the THD+mucopexy technique applicable in most cases. Correct manipulation of the instruments, precision in dearterization, mucopexy of the rectal mucosa and submucosa are imperative for achieving excellent results.